Spondylodiscitis in Pediatric Age: A Retrospective Cohort Study. Issue 7 (7th June 2022) - Cavalieri, Stefano; Pessina, Benedetta; Indolfi, Giuseppe; Galli, Luisa; Trapani, Sandra
Abstract : Background: Pediatric spondylodiscitis is rare, hardly diagnosed and treated due to the nonspecificity of clinical presentation and laboratory investigations, difficulty of etiologic identification and lack of management guidelines. Methods: A retrospective study was conducted on 29 children with spondylodiscitis. Clinical, hematic and radiologic data were collected and compared between 2 age-subgroups (below and from 4 years old on) to investigate age-related differences. Epidemiologic, management and follow-up data were also described. Results: Slight male predominance and a peak of incidence <2 years were observed. Symptoms were significantly differently distributed in the 2 age-subgroups: children <4 years showed mainly refusal/inability to sit or bear weight, irritability, limping and poor general conditions; children ≥4 years most frequently had back pain and fever, and pain upon palpation of the spine. The lumbar spine and more than 1 vertebra were most frequently involved. Median diagnostic delay of 12 days was observed, without significant difference between age-subgroups, and delay >2 months was always associated with multivertebral involvement and complications. All children were treated with broad-spectrum antibiotics for a median of 12 weeks. Only in 1 complicated case, surgical treatment was also required. Conclusions: The clinical presentation of spondylodiscitis may be age-specific, with younger children often exhibiting subtle signs and symptoms. Broad-spectrum antibiotics covering for Staphylococcus aureus should be initiated as soon as possible and performed many weeks, being effective in treating the infection without clinical sequelae, even in patients with comorbidities. Surgical treatment should be reserved for complicated cases with neurologic involvement.